OPTIMIZATION OF JAVANESE LANGUAGE LEARNING THROUGH STORY ADVENTURE GAME - Maula Yudhananta, Naufal; WIJAYANTI, ESTI; CHAMID, AHMAD ABDUL (Tekmapro, 2025)
This research addresses the critical decline in Javanese language usage among younger generations, with only 45% of Central Javanese children actively using the language in daily communication. The study aims to develop and evaluate "Story Adventure of Cakra: Javanese Language," an educational game designed to optimize Javanese language learning for elementary school students aged 7-12 years. The research employed a qualitative methodology involving interviews with students and teachers, participatory observation, and the Game Development Life Cycle (GDLC) framework using Construct 3 engine. The game integrates adventure gameplay mechanics with comprehensive Javanese language instruction, featuring interactive storytelling, script learning modules, cultural elements including unggah-ungguh etiquette and wayang stories, and assessment quizzes. The implementation encompasses four main components: an intuitive user interface with traditional Javanese aesthetics, educational content covering aksara angka, aksara swara, aksara sandangan, and aksara Jawa, engaging adventure gameplay where players control character Cakra to collect script items while avoiding monsters, and comprehensive evaluation systems. Blackbox testing demonstrated 100% functionality validation across all game components, confirming technical reliability and educational effectiveness. The findings reveal that gamification strategies successfully transform traditional language instruction into engaging interactive experiences, bridging conventional teaching methods with contemporary digital learning preferences. This research contributes significantly to educational technology by demonstrating how innovative technological solutions can revitalize interest in regional language preservation while providing measurable learning outcomes for cultural heritage sustainability. Keywords: Javanese language learning, educational game, cultural preservation, gamification, story adventure